Some lessons from history: Morphomes in diachrony - Maiden, M (Oxford University Press, 2016)
What follows informally recounts some ‘lessons I have learned’ from several years spent exploring and describing in close detail the history of the inflectional morphology of the Romance verb.1 This programme of research, which has considered the entire range of Romance languages and dialects, and in as much historical depth and comparative breadth as possible, has been concerned in particular to identify, and describe the development of, a number of phenomena for which it can be argued that they are clear-cut,2 unambiguous cases of ‘morphomes’ in the sense of Aronoff; phenomena, that is, for which extramorphological (phonological or morphosyntactic) synchronic conditioning can be ruled out. Reproduction of all the relevant arguments would require far more space than I have here, and they have been published elsewhere. This is not to say, of course, that these arguments are selfevidently correct or that all morphologists would necessarily be persuaded by them (far from it), but I am interested here in standing back and developing some general reflections on what I believe the unusual comparative breadth and historical depth offered by the descriptive literature3 on Romance languages has to offer for the study of morphomes. The principal lessons that have emerged from the diachronic observation of Romance verb morphology seem to me to be the following: i. Diachrony can provide evidence for the psychological reality of putative morphomes. ii. Diachrony can be used as a diagnostic of the synchronically morphomic nature of some pattern of alternation. iii. Typological comparison can serve to falsify the putatively morphomic status of some pattern of alternation iv. Speakers do not especially prefer ‘non-morphomic’ over ‘morphomic’ patterns. v. An alternation pattern can be morphomic even when it appears to be phonologically conditioned. Each of these findings will be explained and illustrated at least in outline4 in the following sections. In conclusion, I shall briefly present some thoughts on why morphomes persist diachronically, which I shall relate to the observation that all morphomes seem to originate in allomorphy affecting lexical roots.